Trait-based cue Utilization and initial skill acquisition: implications for models of the progression to expertise - Wiggins, Mark W.; Brouwers, Sue; Davies, Joel; Loveday, Thomas (Frontiers in Psychology, 2014)
The primary aim of this study was to examine the role of cue utilization in the initial acquisition of psychomotor skills. Two experiments were undertaken, the first of which examined the relationship between cue utilization typologies and levels of accuracy following four simulated, power-off landing trials in a light aircraft simulator. The results indicated that higher levels of cue utilization were associated with a greater level of landing accuracy following training exposure. In the second study, participants’ levels of cue utilization were assessed prior to two 15 minute periods during which they practiced take-offs and landings using a simulated Unmanned Aerial Vehicle (UAV). Consistent with Study 1, the outcomes of Study 2 revealed a statistically significant relationship between levels of cue utilization and the number of trials to criterion on the take-off task, and the proportion of successful trials during both take-off and landing. In combination, the results suggest that the capacity for the acquisition and the subsequent utilization of cues is an important predictor of skill acquisition, particularly during the initial stages of the process. The implications for theory and applied practice are discussed.